2014
DOI: 10.1002/sia.5362
|View full text |Cite
|
Sign up to set email alerts
|

Stable aqueous dispersion of magnetic iron oxide core–shell nanoparticles prepared by biocompatible maleate polymers

Abstract: A new method is applied to prepare stable aqueous dispersion of magnetic iron oxide nanoparticles (MNPs) by biocompatible maleate polymers. Fe 3 O 4 magnetic core-shell nanoparticles are obtained via forming an inclusion complex between carboxylic acid groups of maleated biocompatible polymers shell and Fe 3 O 4 MNPs core surface. Maleate polymers are synthesized via esterification of poly(ethylene glycol), poly(vinyl alcohol) and starch with maleic anhydride (MA). The Fe 3 O 4 magnetic core-shell nanoparticle… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
8
0

Year Published

2015
2015
2021
2021

Publication Types

Select...
5
2
1

Relationship

1
7

Authors

Journals

citations
Cited by 13 publications
(8 citation statements)
references
References 36 publications
0
8
0
Order By: Relevance
“…The bands related to carboxylic species were not observed on Fe 3 O 4 ,e ven before the hydrogenation step (plot not included), suggesting that the surface of this commercial sample were not susceptible for deposition of carboxylate specieso r to form complexes,a lthough formation of carboxylate acidic group complexes with Fe 3 O 4 nanoparticles [100][101][102] has been reported.T he reference impregnatedo nF eO and Fe 2 O 3 showed weak IR bands at frequenciesc omparable to the 15/5 catalyst. It has been reported that the iron cations Fe 2 + and Fe 3 + can separately form complexes with carboxylate ligand groups.…”
Section: Ex Situ Tem Characterisation:fresh and Used Catalystmentioning
confidence: 97%
“…The bands related to carboxylic species were not observed on Fe 3 O 4 ,e ven before the hydrogenation step (plot not included), suggesting that the surface of this commercial sample were not susceptible for deposition of carboxylate specieso r to form complexes,a lthough formation of carboxylate acidic group complexes with Fe 3 O 4 nanoparticles [100][101][102] has been reported.T he reference impregnatedo nF eO and Fe 2 O 3 showed weak IR bands at frequenciesc omparable to the 15/5 catalyst. It has been reported that the iron cations Fe 2 + and Fe 3 + can separately form complexes with carboxylate ligand groups.…”
Section: Ex Situ Tem Characterisation:fresh and Used Catalystmentioning
confidence: 97%
“…Starch-maleate-MNPs stable aqueous dispersion is prepared as reported previously [28]. Briefly, 100 mg of starch-maleate is dissolved in 10 mL deionized water.…”
Section: Synthesis Of Starch-maleate-mnps Ferrofluidmentioning
confidence: 99%
“…1 H and 13 C NMR spectra (chloroform-d or dimethyl sulfoxide-d 6 ) were obtained on a Varian 300 MHz or Bruker 500 MHz NMR spectrometer in tubes with 5 mm exterior diameters. FTIR analysis was performed using a Smart iTR ATR sampling accessory for the Nicolet iS10 spectrometer with a diamond crystal [Thermo Scientific, Massachusetts, U.S.A.].…”
Section: ■ Materials and Methodsmentioning
confidence: 99%